Hybrid energy storage system energy management method based on smooth control - SHEN MAOJUN (2018)
The invention discloses a hybrid energy storage system energy management method based on smooth control. The method comprises three portions of the smooth control, hybrid energy storage limit value management and super-capacitor terminal voltage precontrol. In the invention, by using the hybrid energy storage system energy management method, a super capacitor and a cell are used to compensate a high frequency component and a middle and low frequency component in a renewable energy output power fluctuation; and based on a traditional limit value management method, the super-capacitor terminal voltage precontrol is introduced. According to a residual capacity of the super capacitor and a charge and discharge state, output power of the super capacitor and the cell is corrected so that the super capacitor can be prevented from stopping working because a terminal voltage reaches upper and lower limits. 本发明公开了种基于平滑控制的混合储能系统能量管理方法，包括平滑控制、混合储能限值管理、超级电容端电压预先控制三个部分。本发明所述混合储能系统能量管理方法分别利用超级电容与电池补偿可再生能源输出功率波动中的高频分量和中低频分量，